Features of morphological and functional characteristics and physical preparedness of sprinters 15-16 years old, specializing in various swimming methods - Politko, E.; Sheyko, L. (Slobozhanskyi herald of science and sport, 2020)
Purpose: to develop model morphological and functional characteristics and indicators of physical preparedness of 15-16-year-old sprint swimmers specializing in various swimming methods.